The Relationship between Metabolic Control Status and Microalbuminuria in Pediatric Diabetes Mellitus Patients at Dr. M. Djamil General Hospital, Padang, Indonesia - Fatmah Sindi; Aumas Pabuti; Eka Agustia Rini (HM Publisher, 2023)
Background: Diabetes mellitus (DM) is a complex metabolic disorder that can cause many complications. HbA1c measurement can help monitor long-term serum glucose regulation. Microalbuminuria in DM patients is a risk factor for these complications, so evaluation of risk factors for prevention is necessary. This study aimed to determine the relationship between metabolic control status and microalbuminuria in pediatric diabetes mellitus patients at Dr. M. Djamil General Hospital, Padang, Indonesia. Methods: This study is an analytic observational study with a cross-sectional approach. A total of 34 children with DM aged 1-18 years participated in this study. Sampling was carried out using the consecutive sampling method at the pediatric polyclinic of Dr. M. Djamil General Hospital, Padang, Indonesia, from November 2021-April 2022. Metabolic control status was assessed by measuring HbA1C levels and microalbuminuria by measuring the urine albumin-creatinine ratio. Data analysis used the Chi-square test, with a p-value <0.05. Results: The average respondent was 13.2 ± 3.3 years old with a duration of suffering from DM 2.5 ± 2 years. Most of the respondents were male (52.9%), suffered from type 1 DM (94.1%), had uncontrolled metabolic control status (82.3%), had a normal creatine albumin ratio (82.4%), never had diabetic ketoacidosis (79.4%), had no family history of DM (85.3%) and had normal blood pressure (94.1%). It is known that the average urea and creatinine are within normal limits. The average HbA1c value is 11.9 ± 3.39%. The median urine creatine albumin ratio was 7.98 (0-255.74) ug/mg. Microalbuminuria in uncontrolled metabolic control status was found in as much as 17.6%, whereas in controlled metabolic control status, no microalbuminuria was found. Statistically, there is no significant relationship (p>0.05). Conclusion: There is no relationship between metabolic control status and microalbuminuria in pediatric diabetes mellitus patients at Dr. M. Djamil General Hospital, Padang, Indonesia.